Pedagogic and Professional Competence of English Teachers at Junior High School - Achyana Sulfiah; Bahrun Amin; Nurqalbi Nurqalbi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2022)
The objective of the research to find out Pedagogic and Professional of English teachers at junior high school in Bulukumba. This research is quantitative descriptive. Technique of collecting data use questionnaire. Population is 70 Junior High School with 128 English teachers, technique sampling is Proportionate stratified random sampling. Data analysis technique is descriptive data analysis quantitative that is shown in percentage.The research result shown that Pedagogic and Professional competence of English teachers at junior high school in Bulukumba in Category “ Very high Competence “ from seventeen respondents around 94%, and category “ High Competence” from one respondent around 6%.“It can be conclude that Pedagogical and professional competence of English teacher at Junior high school in Bulukumba in Category “ Very High Competence”. The result is English teachers at junior high school in Bulukumba competence both Pedagogic and professional.